The ten-year evaluation of clinical characteristics in congenital lung anomaly in pediatrics; a retrospective study in North of Iran - Narges Lashkarbolouk; Mahdi Mazandarani; Ali Ahani Azari; Somayeh Ghorbani; Lobat Shahkar (BMC, 2024)
Abstract Introduction Congenital lung anomalies (CLA) are a group of anomalies, including congenital cystic adenomatoid malformation (CCAM), bronchopulmonary sequestrations (BPS), congenital lobar emphysema (CLE), and bronchogenic cysts (BC). The prevalence of these rare anomalies has risen in recent years, according to various population-based studies due to advances in fetal ultrasound technology. Method This retrospective study examines the diagnosis of CLA, and was conducted on 72 patients between March 2014 and March 2024 at Taleghani Pediatric Hospital in Gorgan, Iran. Result The average age was 18.8 ± 30.3 months, with the majority being boys (62.5%). Most participants had CCAM (41.7%), followed by CLE (18.1%), BPS (16.7%), pulmonary hypoplasia (9.7%), BC (8.3%), and hybrid lesion (5.6%). The majority of patients were Fars (62.5%), and the average hospitalization days was 9.4 ± 4.5 days. Cardiac anomalies were observed in 19.4% of the patients. 62 patients (86.1%) exhibited respiratory symptoms, and prenatal screening during pregnancy led to the diagnosis in 51 patients (70.8%). Most patients had left lung anomalies (43; 59.7%), and the majority (90.3%) survived. There is a statistically significant relation between needed for surgical treatment and patients' type of pulmonary lesions (p-value: 0.02). In addition, there was a significant relation between the Fars ethnicity and the presence of cardiac anomalies (p-value: 0.04). Conclusion Some CLAs remain undiagnosed or untreated due to the rare nature of congenital lung anomalies. Nevertheless, improvements in ultrasound and other imaging methods will make diagnosing and managing these anomalies during the prenatal period more prevalent, resulting in enhanced understanding.